Antibacterial hydrogel for wound repair as well as preparation method and application of antibacterial hydrogel
By introducing ingredients such as polyphosphor phosphate nanoparticles, shell polycogen, and metal cedication in the introduction of antibacterial hydrogel, using non -common price interactions to form hydrophilic gels with excellent mechanical performance, adhesion performance and antibacterial properties, solved the solution, which solved it, which solved it, which solved it. The problem of insufficient performance of water gel materials has achieved better wound repair effects.
Patent Information
- Application Number
- CN202411519205.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
Existing hydrogel materials for wound repair have poor performance in mechanical properties, adhesion properties and antibacterial properties, making it difficult to cope with complex wound repair challenges.
By introducing ingredients such as polymeric phosphate nanoparticles, shell polycogen, metal cationic ions and other components in antibacterial hydrogel, use non -common price effects such as static electricity interaction, hydrogen bonding, metal ion chewing, etc., to form excellent mechanical properties, and have excellent mechanical performance, and Hydraulic gel with adhesion and antibacterial performance.
It significantly improves the mechanical performance, adhesion performance and antibacterial performance of antibacterial hydrogel, making it more suitable for wound repair, and can effectively respond to complex wound repair challenges.
Smart Images

Figure CN119345452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to an antibacterial hydrogel for wound repair and a preparation method and application thereof. Background Art
[0002] Hydrogel is one of the materials that has attracted much attention in the field of biomedical materials. It is a colloid that is composed of a three-dimensional network of hydrophilic polymers and is rich in a large amount of water or biological fluids. Hydrogels usually have good biocompatibility, mechanical properties similar to those of human tissues, certain swelling properties and adhesion properties, which give hydrogels great application potential in the field of wound repair. Compared with traditional wound dressings such as gauze, bandages, and cotton, when hydrogels are used as wound dressings for wound repair, they can provide a relatively moist microenvironment for wound repair. The appropriate swelling properties allow the hydrogel to absorb excess exudate from the wound without compressing the wound due to excessive expansion, slowing down the wound repair process. In addition, the adhesion and mechanical properties of the hydrogel enable it to adapt to the elasticity of human tissues to achieve adhesion, making the application and removal of the hydrogel superior to traditional wound dressings.
[0003] Polyphosphate (PolyP, Polyphosphates) is an ancient molecule widely present in organic life and has a variety of physiologically active functions. It is usually formed by tens to thousands of phosphate groups connected by high-energy phosphate bonds. It is a negatively charged linear chain polymer. Studies have shown that when polyphosphate is used in the field of wound repair, it can accelerate the speed of wound repair through various pathways and mechanisms, but its bioavailability is mostly in the form of polyphosphate nanoparticles. Using histological methods, researchers found that when polyphosphate nanoparticles were used to treat wounds, the speed of new granulation tissue formation at the wound was significantly increased, and the formation of new microvessels was also greatly accelerated, proving that polyphosphate nanoparticles can stimulate the growth of vascular endothelial cells to accelerate the formation of new blood vessels. In addition, the presence of polyphosphate nanoparticles can also upregulate the expression of genes related to collagen fiber production, α-smooth muscle actin (α-SMA) and plasminogen activator inhibitor-1 (PAI-1), thereby promoting collagen synthesis and maintaining the body's normal coagulation function, so that wound repair can proceed smoothly. In addition, when polyphosphate nanoparticles exert their biological activity, they will form an active form called a condensed state, and the formation of this condensed state has a phase transition process. During the phase transition process, polyphosphate nanoparticles can encapsulate bacteria or viruses infected by the wound to a certain extent, and the high-density charge state of the condensed state can further kill bacteria and viruses, reducing the possibility of wound repair process disorders caused by wound infection. In short, polyphosphate nanoparticles have a variety of excellent properties and have great value in the field of wound repair.
[0004] There are some reports on the application of polyphosphate nanoparticles in the field of wound repair, such as collagen wound dressings prepared by simply doping zinc-polyphosphate nanoparticles, and weak hydrogel materials prepared by simply mixing alginate, oxidized alginate, gelatin and zinc-polyphosphate nanoparticles, all of which can promote wound repair. However, the above materials have poor performance in mechanical properties, adhesion properties and antibacterial properties, which are not enough to cope with the increasingly complex challenges of wound repair. Therefore, it is of great significance to develop an antibacterial hydrogel with excellent mechanical properties, adhesion properties and antibacterial properties. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides an antibacterial hydrogel for wound repair and a preparation method and application thereof. Under the action of a crosslinking agent and a thermal initiator, the methacryloylethyl sulfobetaine in the antibacterial hydrogel of the present invention is in situ polymerized through a thermal initiation process to form a three-dimensional network of the antibacterial hydrogel; polyphosphate nanoparticles, chitosan biguanide, and metal cations are uniformly dispersed in the antibacterial hydrogel system through various non-covalent interactions such as electrostatic interaction, hydrogen bonding, and metal ion chelation, thereby improving the mechanical properties, adhesion properties, and antibacterial properties of the antibacterial hydrogel, so that it can be better used as an antibacterial material in the field of wound repair.
[0006] The technical solution of the present invention is as follows:
[0007] An antibacterial hydrogel for wound repair. The raw materials of the antibacterial hydrogel include polyphosphate nanoparticles, chitosan biguanide, methacryloylethyl sulfobetaine, metal cations, a crosslinking agent, a thermal initiator and water.
[0008] Furthermore, the polyphosphate nanoparticles are calcium-polyphosphate nanoparticles, and the number of phosphate groups is 40 to 120; the concentration of the polyphosphate nanoparticles in water is 4 to 6 mg / mL.
[0009] Furthermore, the mass percentage of the chitosan biguanide in water is 2-6wt%.
[0010] Furthermore, the concentration of the methacryloylethyl sulfobetaine in water is 1.5 to 3 mol / L.
[0011] Furthermore, the metal cation is a zinc ion or a magnesium ion; and the concentration of the metal cation in the antibacterial hydrogel is 0.03-0.05 mol / L.
[0012] Furthermore, the cross-linking agent is selected from at least one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide; the amount of the cross-linking agent is 0.25-0.5% of the molar amount of methacryloylethyl sulfobetaine.
[0013] Furthermore, the thermal initiator is selected from at least one of ammonium persulfate and potassium persulfate; the amount of the thermal initiator is 0.25 to 0.5% of the molar amount of methacryloylethyl sulfobetaine.
[0014] A method for preparing the antibacterial hydrogel, the method comprising the following steps:
[0015] (1) preparing a prepolymer solution: adding a crosslinking agent and a thermal initiator to a suspension containing polyphosphate nanoparticles, chitosan biguanide, methacryloylethyl sulfobetaine, and metal cations at room temperature to obtain a prepolymer solution;
[0016] (2) Initiating gelation: subjecting the prepolymer solution to a heat-induced in-situ polymerization treatment to obtain the antibacterial hydrogel.
[0017] Furthermore, in step (2), the temperature of the thermally initiated in-situ polymerization treatment is 50-70° C., and the time is 1.5 to 3 hours.
[0018] An application of the antibacterial hydrogel, wherein the antibacterial hydrogel is used to prepare a product for promoting wound repair.
[0019] The beneficial technical effects of the present invention are:
[0020] The present invention utilizes chemical means to graft biguanide groups onto chitosan. The protonated biguanide groups are positively charged, which increases the positive charge density of chitosan and improves the water solubility of chitosan. The preparation process of chitosan hydrogel is simplified. The positive charge of the modified chitosan can be enhanced through the synergistic effect of the two, and the bacterial cell membrane can be effectively destroyed through electrostatic interaction, thereby obtaining a more powerful broad-spectrum antibacterial property.
[0021] The polyphosphate nanoparticles prepared by the present invention have excellent biological properties, and their high-energy phosphate bonds can provide energy for ATP-related energy metabolism processes. In the field of wound repair, Ca-PolyP can not only promote the differentiation of keratinocytes to accelerate the process of skin re-epithelialization, but also accelerate the wound repair process by regulating coagulation, stimulating microangiogenesis, and promoting the growth of granulation tissue and collagen fibers. It also plays an antibacterial role by affecting key enzymes related to polyphosphate metabolism in bacteria and treats wound infections.
[0022] The present invention introduces chitosan biguanide, polyphosphate nanoparticles, metal cations, and zwitterions into the hydrogel system, thereby enhancing the non-covalent interactions in the antibacterial hydrogel system, such as electrostatic interactions, hydrogen bond interactions, metal ion chelation, etc., while achieving enhanced antibacterial effects and promoting wound repair effects, and effectively improving the mechanical properties and adhesion properties of the antibacterial hydrogel, so that it meets the performance requirements of the hydrogel used as a wound dressing.
[0023] The antibacterial hydrogel of the present invention is prepared by mixing various components in a one-pot method to form a prepolymer solution, and then heating the prepolymer solution in a water bath at a constant temperature for a certain period of time to obtain the antibacterial hydrogel containing polyphosphate nanoparticles. The method is simple and easy to operate.
[0024] Among the raw material components of the antibacterial hydrogel of the present invention, polyphosphate nanoparticles are the active form of biological macromolecules that already exist in living bodies and have excellent biocompatibility. Other components involved in the antibacterial hydrogel system, chitosan derivatives—chitosan biguanide and methacryloylethyl sulfobetaine, are commonly used ingredients or monomers in the field of biomedical materials and also have good biocompatibility. The concentrations of added metal cations are all within the safe range, so the prepared antibacterial hydrogel has good biocompatibility.
[0025] Compared with previously reported wound repair hydrogels, the antibacterial hydrogel prepared by the present invention has better mechanical properties, adhesion properties, antibacterial properties, excellent biocompatibility and outstanding repair-promoting ability, can cope with increasingly complex wound repair challenges, and can be used as an antibacterial material in the field of wound repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the calcium-polyphosphate nanoparticles prepared in Example 1 of the present invention.
[0027] Figure 2 The tensile stress-strain diagram of the antibacterial hydrogel prepared in Examples 2-3 of the present invention and Comparative Example 1.
[0028] Figure 3 This is a pigskin lap shear adhesion curve of the antibacterial hydrogel prepared in Examples 2-3 of the present invention and Comparative Example 1.
[0029] Figure 4 This is a graph showing the antibacterial test results of the antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1.
[0030] Figure 5 The tensile stress-strain diagrams of the antibacterial hydrogels prepared in Examples 2, 4-8 and Comparative Examples of the present invention.
[0031] In the figure: a, is the tensile stress-strain diagram of the antibacterial hydrogel prepared by Examples 2, 4-5 and Comparative Examples 2-3 of the present invention; b, is the tensile stress-strain diagram of the antibacterial hydrogel prepared by Examples 2, 6 and Comparative Examples 4-6 of the present invention; c, is the tensile stress-strain diagram of the antibacterial hydrogel prepared by Examples 2, 7-8 and Comparative Examples 7-8 of the present invention.
[0032] Figure 6 This is a graph showing the cytotoxicity results of the antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1.
[0033] Figure 7 This is a diagram showing the in vivo evaluation results of wound repair of the antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0034] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0035] The sodium-polyphosphate (Na-PolyP) in the following examples has 45 phosphate groups and is purchased from Chili Pepper Reagents with a catalog number of NCP001; polyethylene glycol diacrylate is purchased from Aladdin Reagents with a catalog number of P131592;
[0036] The chitosan in the following examples was commissioned to Qingdao Yunzhou Biotechnology Co., Ltd. to be customized according to Mw=20-50 kDa and a deacetylation degree of about 92%.
[0037] The preparation methods of the sodium-polyphosphate solution and calcium chloride solution in the following embodiments are as follows:
[0038] Na-PolyP solution: Dissolve 10 g of sodium-polyphosphate (Na-PolyP) in 500 mL of deionized water to obtain a Na-PolyP solution with a concentration of 20 g / L;
[0039] CaCl2 solution: Dissolve 14 g of anhydrous calcium chloride in 250 mL of deionized water to obtain a CaCl2 solution with a concentration of 56 g / L.
[0040] The mass percentage of chitosan biguanide in the present invention refers to the mass percentage of chitosan biguanide aqueous solution, and the calculation method is: 壳聚糖双胍 =m 壳聚糖双胍 ÷(m 水 +m 壳聚糖双胍 )×100%; where ω 壳聚糖双胍 Indicates the mass percentage of chitosan biguanide, in %; m 壳聚糖双胍 Indicates the mass of chitosan biguanide in g; m 水 Indicates the mass of deionized water in g.
[0041] Example 1
[0042] Preparation of calcium-polyphosphate nanoparticles and chitosan biguanide raw materials:
[0043] (1) Preparation of calcium-polyphosphate nanoparticles, the preparation method thereof is as follows:
[0044] At room temperature, 500 mL of 20 g / mL Na-PolyP solution was placed in a conical flask and stirred at a speed of 600 r / min. 250 mL of 56 g / mL CaCl2 solution was added dropwise at a speed of 1 mL / min using a syringe pump. After the addition was completed, the reaction was continued to stir for 4 h (keeping the pH value of the reaction system at 10), and then the filter residue was obtained by filtration. The residue was washed three times with anhydrous ethanol to obtain a solid powder, which was dried at 60 ° C for 2 h to obtain calcium-polyphosphate nanoparticles (Ca-PolyP NPs).
[0045] The morphology of calcium-polyphosphate nanoparticles was observed by Hitachi Regulus SU8230 high-resolution cold field emission scanning electron microscope. Figure 1 As shown. Figure 1 The results show that the diameter of calcium-polyphosphate nanoparticles is about 200 nm.
[0046] (2) Preparation of chitosan biguanide, the preparation method thereof is as follows:
[0047] Take 1g of chitosan and add it to a 250mL three-necked flask. While stirring, slowly add 100mL of 1% HCl aqueous solution and continue stirring at room temperature for 30min. Then add 1.06g of dicyandiamide, then transfer the three-necked flask to a 90℃ oil bath and heat under reflux for 3h. After the reaction is completed, pour the reaction solution into 200mL of cold anhydrous ethanol, wait for the product to precipitate, and filter to obtain a crude product. Wash the crude product 3 times with anhydrous ethanol (200mL each time), and place the obtained product in a vacuum drying oven to dry for 3h to obtain the final product.
[0048] Example 2
[0049] An antibacterial hydrogel for wound repair, the preparation method of which is as follows:
[0050] (1) 60 mg of the Ca-PolyP NPs prepared in Example 1 was weighed, 10 mL of deionized water was added, and ultrasonic treatment was performed for 30 min to obtain a uniformly dispersed Ca-PolyP NPs suspension with a concentration of 6 mg / mL; 3 mL of the Ca-PolyP NPs suspension was added with 0.192 g of chitosan biguanide (the mass percentage of chitosan biguanide relative to water was 6%), and stirred until the chitosan biguanide was completely dissolved; then 1.6761 g of methacryloylethyl sulfobetaine, 0.0204 g of anhydrous zinc chloride (Zn 2+ The concentration in water is 0.05 mol / L), 8 μL of polyethylene glycol diacrylate (mass is 0.00896 g) and 0.0034 g of ammonium persulfate, and the solid is completely dissolved by ultrasonic and stirring treatment to obtain a prepolymer solution.
[0051] (2) Initiation of gelation: The prepolymer solution obtained in step (1) was injected into a sealed glass mold with a length of 15 cm, a width of 10 cm, and a thickness of 1.5 mm, and the air bubbles were exhausted. The sealed glass mold was then placed in a 60°C constant temperature water bath for thermal initiation for 2 h to solidify it into a thin sheet of hydrogel. The obtained antibacterial hydrogel containing polyphosphate nanoparticles was denoted as Zn 2+ -Hydrogel.
[0052] Example 3
[0053] The preparation method of Example 3 is basically the same as that of Example 2, except that 0.0143 g of anhydrous magnesium chloride is used in step (1) of Example 3 to replace 0.0204 g of anhydrous zinc chloride in Example 2, and the rest of the contents remain unchanged.
[0054] Embodiment 4-5
[0055] The preparation method of Example 4-5 is basically the same as that of Example 2, except that the amounts of chitosan biguanide used in step (1) of Example 4-5 are 0.064 g (the mass percentage of chitosan biguanide relative to water is 2%) and 0.128 g (the mass percentage of chitosan biguanide relative to water is 4%), respectively, and the rest of the contents remain unchanged.
[0056] Example 6
[0057] The preparation method of Example 6 is basically the same as that of Example 2, except that the concentration of the Ca-PolyP NPs suspension prepared in step (1) of Example 6 is 4 mg / mL, and the rest of the contents remain unchanged.
[0058] Embodiment 7-8
[0059] The preparation method of Example 7-8 is basically the same as that of Example 2, except that the amount of anhydrous zinc chloride used in step (1) of Example 7-8 is 0.0122 g (Zn 2+ The concentration in water is 0.03 mol / L), 0.0163 g (Zn 2+ The concentration in water is 0.04mol / L), and the rest of the contents remain unchanged.
[0060] Comparative Example 1
[0061] The preparation method of Comparative Example 1 is substantially the same as that of Example 2, except that 0.0166 g of anhydrous calcium chloride is used in step (1) of Comparative Example 1 to replace 0.0204 g of anhydrous zinc chloride in Example 2, and the rest of the contents remain unchanged.
[0062] Comparative Examples 2-3
[0063] The preparation method of Comparative Example 2-3 is basically the same as that of Example 2, except that the amounts of chitosan biguanide used in step (1) of Comparative Example 2-3 are 0 and 0.256 g respectively (the mass percentage of chitosan biguanide relative to water is 8%), and the rest of the contents remain unchanged.
[0064] Comparative Examples 4-6
[0065] The preparation method of Comparative Example 4-6 is basically the same as that of Example 2, except that the concentrations of the Ca-PolyP NPs suspension prepared in step (1) of Comparative Example 4-6 are 2 mg / mL, 8 mg / mL, and 10 mg / mL, respectively, and the rest of the contents remain unchanged.
[0066] Comparative Examples 7-8
[0067] The preparation method of Comparative Examples 7-8 is substantially the same as that of Example 2, except that the amount of anhydrous zinc chloride used in step (1) of Comparative Examples 7-8 is 0.0040 g (Zn 2+ The concentration in water is 0.01mol / L), 0.0082g(Zn 2+ The concentration in water is 0.02mol / L), and the rest of the contents remain unchanged.
[0068] Comparative Example 9
[0069] The preparation method of Comparative Example 9 is basically the same as that of Example 2, except that the temperature of thermal initiation in step (2) of Comparative Example 9 is 40° C., and the rest of the contents remain unchanged.
[0070] Results: The hydrogel in Comparative Example 9 did not gel during the preparation process.
[0071] Test Case
[0072] The mechanical properties testing method is as follows: the prepared antibacterial hydrogel sample is made into a rectangular specimen (length 30 mm, width 5 mm, thickness 1.5 mm), and tested using a universal testing machine equipped with a 200N sensor. The stretching speed is set to 50 mm / min, and the hydrogel is stretched until it breaks, and the stress-strain curve is recorded.
[0073] The adhesion performance test method is as follows: The adhesion performance of the antibacterial hydrogel is quantitatively tested using a lap shear test. The antibacterial hydrogel sample is made into a rectangular specimen (length 20 mm, width 15 mm, thickness 1.5 mm), and the sample is adhered to the pig skin to form a sandwich composite structure. A universal testing machine is used to vertically stretch the adhesive part at a stretching rate of 50 mm / min until it is peeled off. The adhesion strength of the antibacterial hydrogel is the ratio of the maximum load in the stress-strain curve to the corresponding adhesion area.
[0074] The antibacterial performance test method is as follows: the antibacterial hydrogel sample is made into a circular specimen with a diameter of 10mm and a thickness of 1.5mm. After UV sterilization, the specimen is placed in a 24-well plate with a pre-cultured bacterial suspension with a concentration of 106CFU / mL and a volume of 250μL, and transferred to a 37℃ constant temperature incubator for shaking co-culture for 24h (100rpm / min). After the culture is completed, 50μL of the co-culture solution is evenly spread on the solid culture medium in each group, and the solid culture medium is placed in a 37℃ constant temperature incubator for incubation for 24h and then taken out to observe and take pictures to record the bacterial growth on the solid culture medium.
[0075] The cytotoxicity test method is as follows: take the test solution and perform the extraction method specified in GB / T16886.5-2017. Specifically: after the antibacterial hydrogel sample is sterilized by ultraviolet, the sample is extracted at a ratio of 0.1g sample / 1mL extraction medium. The extraction medium is DMEM culture medium containing serum. The extract is prepared at 37±1°C for (24±2)h to obtain the antibacterial hydrogel test solution to be tested. The extract is then used to completely replace the DMEM culture medium containing serum for the culture of L929 cells (the culture time is 24h / 48h). The survival rate of L929 cells is detected by the CCK-8 method. The cytotoxicity of the antibacterial hydrogel is characterized by the survival rate of L929 cells.
[0076] In vivo evaluation method for wound repair: Healthy SPF-grade male SD rats weighing approximately 220g to 250g were randomly selected, and a full-thickness skin defect Staphylococcus aureus infection model (10mm in diameter) was established in type 1 diabetic rats. After 24 hours, each group of antibacterial hydrogel samples with a length and width of 10mm and a thickness of 1.5mm were attached to the wound. The wounds of each group were photographed and recorded on the 1st, 3rd, 5th, 7th, 14th and 21st days.
[0077] (1) Effect of metal ion types on the mechanical properties of antibacterial hydrogels
[0078] The antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1 were tested for their mechanical properties. Figure 2 As shown. Figure 2 It can be seen that adding Zn 2+ , Ca 2+ Mg 2+ The antibacterial hydrogels have good mechanical properties. 2+ -The elongation at break of the hydrogel is 800% and the tensile strength is 70 kPa; Ca 2+ -The elongation at break of the hydrogel is 700% and the tensile strength is 75 kPa; Mg 2+ -The elongation at break of the hydrogel is 800% and the tensile strength is 95 kPa.
[0079] (2) Effect of metal ion type on the adhesion properties of antibacterial hydrogels
[0080] The antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1 were tested for their adhesion properties. Figure 3 As shown. Figure 3 It can be seen that adding Zn 2+ , Ca 2+ Mg 2+ The adhesion strengths of the antibacterial hydrogels to pig skin were 13.8 kPa, 13.1 kPa and 10.4 kPa, respectively, all greater than 10 kPa.
[0081] (3) Effect of metal ion types on the antibacterial properties of antibacterial hydrogels
[0082] The antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1 were tested for their antibacterial properties. Figure 4 As shown. Figure 4 It can be seen that compared with the blank control group, the addition of Zn 2+ , Ca 2+ Mg 2+ The antibacterial hydrogel showed obvious antibacterial effects against Escherichia coli, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus.
[0083] (4) Effect of chitosan biguanide dosage on the mechanical properties of antibacterial hydrogels
[0084] The antibacterial hydrogels prepared in Examples 2, 4-5 and Comparative Examples 2-3 of the present invention were tested for their mechanical properties. Figure 5 As shown in a. Figure 5 As can be seen from the results of Figure a, with the increase of chitosan biguanide dosage, the tensile properties and tensile strength of the antibacterial hydrogel are gradually improved. However, in the actual experimental process, we found that when the concentration of chitosan biguanide reached 8%wt, the prepared hydrogel prepolymer solution was very viscous, and the bubbles generated by stirring in the prepolymer solution could hardly be removed. The subsequent injection of the prepolymer solution was also very difficult, which ultimately led to a large degree of uncontrollability of the prepared hydrogel properties. Therefore, the dosage of chitosan biguanide has a significant effect on the mechanical properties of the antibacterial hydrogel. When the dosage of chitosan biguanide is 2-6wt%, the mechanical properties of the antibacterial hydrogel are better, and the mechanical properties of the antibacterial hydrogel prepared when the dosage of chitosan biguanide is 6%wt are the best.
[0085] (5) Effect of Ca-PolyP NPs suspension concentration on the mechanical properties of antibacterial hydrogels
[0086] The antibacterial hydrogels prepared in Examples 2 and 6 of the present invention and Comparative Examples 4-6 were tested for their mechanical properties. Figure 5 As shown in b. Figure 5 From the results in Figure b, we can see that with the increase of Ca-PolyP NPs concentration, the tensile strength of the hydrogel gradually increases, and the elongation at break shows a trend of first increasing and then decreasing. However, in actual operation, we found that with the increase of Ca-PolyP NPs concentration, its dispersion uniformity gradually decreases. When the concentration of Ca-PolyP NPs reaches 8 mg / mL, the prepared hydrogel shows obvious inhomogeneity, and the color of the hydrogel sample gradually turns white, and the transparency is greatly reduced. Therefore, combined with the mechanical properties test results, the mechanical properties of the antibacterial hydrogel are better when the concentration of Ca-PolyP NPs is 4-6 mg / mL, and the mechanical properties of the antibacterial hydrogel prepared when the concentration of Ca-PolyP NPs is 6 mg / mL are the best.
[0087] (6) Effect of metal ion concentration on mechanical properties of antibacterial hydrogels
[0088] The antibacterial hydrogels prepared in Examples 2, 7-8 and Comparative Examples 7-8 of the present invention were tested for their mechanical properties. Figure 5 c. Figure 5 As can be seen from the results of Figure c, with the increase of metal ion concentration, the elongation at break of the hydrogel gradually increased, and the tensile strength decreased. Considering that the metal ion concentration groups set were all within the safe range, the mechanical properties of the antibacterial hydrogel were better when the metal ion concentration was 0.03-0.05 mol / L, and the antibacterial hydrogel had the best tensile properties at break when the metal ion concentration was 0.05 mol / L.
[0089] (7) Cytotoxicity test of antibacterial hydrogels with different metal ion types
[0090] The antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1 were tested for their cytotoxicity. The results are as follows: Figure 6 As shown. Figure 6 The results show that at 24h, Zn 2+ , Ca 2+ Mg 2+ The L929 cell survival rates of the antibacterial hydrogels were 90.4±1.6%, 99.1±2.3%, and 96.5±1.3%, respectively. At 48h, the cell survival rates were 100.4±2.1%, 98.9±6.0%, and 102.1±6.7%, respectively; the cell survival rates of the three groups of hydrogels were all over 90%, indicating that they all have good biocompatibility. At 48h, the addition of Ca 2+ The cell survival rate of the antibacterial hydrogels was not much different from that of the hydrogels themselves at 24 h, while the addition of Zn 2+ Mg 2+After the antibacterial hydrogels were used for L929 cell culture, the cell survival rate increased. This result indirectly shows that the Ca-PolyP NPs in the three groups of antibacterial hydrogels endowed the hydrogels with the function of promoting cell growth, making them show better biocompatibility. 2+ Mg 2+ The antibacterial hydrogel exhibited better function in promoting cell growth.
[0091] (8) Evaluation of the therapeutic effect of antibacterial hydrogel wound dressing on chronic wounds infected with Staphylococcus aureus
[0092] The antibacterial hydrogels prepared in Examples 2-3 of the present invention and Comparative Example 1 and commercial 3M transparent dressings (article number: 1624W; as a control group) were used as wound dressings in a full-thickness skin defect Staphylococcus aureus infection model of type 1 diabetic rats. The wounds of different groups were photographed and recorded on the 1st, 3rd, 5th, 7th, 14th, and 21st days of the experiment. The results are as follows: Figure 7 As shown. Figure 7 The results show that during the entire wound repair process, each group showed different degrees of bacterial infection in the first three days. 2+ The infection of the antibacterial hydrogel was slightly better than that of the other groups, indicating that the infection model was successfully established and also in line with the Zn 2+ The results of the antibacterial experiment showed that the hydrogel group had the best antibacterial effect. On the 5th day of the experiment, Zn 2+ , Ca 2+ Mg 2+ The bacterial infection of the antibacterial hydrogel was basically eliminated, while the bacterial infection of the control group lasted until the 7th day. 2+ The wounds in the hydrogel-treated group healed almost completely, which was superior to those in the Zn 2+ and Ca 2+ group, while in the control group, obvious wounds could be seen, and no skin appendages such as hair grew, indicating poor wound healing.
[0093] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. An antibacterial hydrogel for wound repair, characterized in that: The raw materials of the antibacterial hydrogel include polyphosphate nanoparticles, chitosan biguanide, methacryloylethyl sulfobetaine, metal cations, a crosslinking agent, a thermal initiator and water.
2. The antibacterial hydrogel according to claim 1, characterized in that: The polyphosphate nanoparticles are calcium-polyphosphate nanoparticles, and the number of phosphate groups is 40-120; the concentration of the polyphosphate nanoparticles in water is 4-6 mg / mL.
3. The antibacterial hydrogel according to claim 1, characterized in that: The mass percentage of the chitosan biguanide in water is 2-6wt%.
4. The antibacterial hydrogel according to claim 1, characterized in that: The concentration of the methacryloylethyl sulfobetaine in water is 1.5-3 mol / L.
5. The antibacterial hydrogel according to claim 1, characterized in that: The metal cation is a zinc ion or a magnesium ion; the concentration of the metal cation in the antibacterial hydrogel is 0.03-0.05 mol / L.
6. The antibacterial hydrogel according to claim 1, characterized in that: The cross-linking agent is selected from at least one of polyethylene glycol diacrylate and N,N'-methylenebisacrylamide; the amount of the cross-linking agent is 0.25-0.5% of the molar amount of methacryloylethyl sulfobetaine.
7. The antibacterial hydrogel according to claim 1, characterized in that: The thermal initiator is selected from at least one of ammonium persulfate and potassium persulfate; the amount of the thermal initiator is 0.25-0.5% of the molar amount of methacryloylethyl sulfobetaine.
8. A method for preparing the antibacterial hydrogel according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) preparing a prepolymer solution: adding a crosslinking agent and a thermal initiator to a suspension containing polyphosphate nanoparticles, chitosan biguanide, methacryloylethyl sulfobetaine, and metal cations at room temperature to obtain a prepolymer solution; (2) Initiating gelation: subjecting the prepolymer solution to a heat-induced in-situ polymerization treatment to obtain the antibacterial hydrogel.
9. The preparation method according to claim 8, characterized in that: In step (2), the temperature of the thermally initiated in-situ polymerization treatment is 50-70° C. and the time is 1.5 to 3 hours.
10. An application of the antibacterial hydrogel according to any one of claims 1 to 7, characterized in that: The antibacterial hydrogel is used for preparing a product for promoting wound repair.